Bridging the Gap or Perpetuating Poverty? The Complex Effects of Non-Cash Food Assistance on Food Security - Husnul Mubarok; Tri Haryanto (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2026)
Objective: This study aims to examine the impact of the Non-Cash Food Assistance Program on food consumption and food insecurity. The primary objective is to assess whether BPNT improves nutritional intake while also influencing households’ perceived food security, thereby contributing to the evaluation of social protection policies. Design/Methods/Approach: The study adopts a quantitative approach using Propensity Score Matching (PSM) to compare the beneficiaries and non-beneficiaries. The analysis focuses on key outcome variables, including calorie, protein, fat, and carbohydrate intake, as well as the Food Insecurity Experience Scale (FIES) score as a subjective measure of food insecurity. The PSM method is employed to reduce selection bias and generate more robust estimates of program impact. Findings: The results indicate that participation in the Non-Cash Food Assistance program significantly improves all measured nutritional intake indicators, including calories, protein, fat, and carbohydrates. However, FIES scores decline among beneficiaries, suggesting a lower perceived level of food security. This divergence between objective outcomes (nutritional intake) and subjective indicators (perceived food insecurity) points to potential psychological effects of assistance programs, particularly when they are not accompanied by empowerment-oriented interventions. Originality/Value: This study contributes to the literature by highlighting the gap between objective and subjective impacts of food assistance programs. By jointly analyzing nutritional indicators and FIES within a PSM framework, it offers a more nuanced understanding of social assistance effectiveness and program sustainability in developing-country contexts. Practical/Policy implication: The findings underscore the importance of policy design that goes beyond meeting short-term nutritional needs. Policymakers should integrate food assistance with empowerment measures that enhance long-term resilience, including improved economic independence, a stronger sense of security, and a fair and humane graduation system. Such an approach can help ensure that BPNT not only alleviates immediate food shortages but also supports sustainable food security outcomes.